Antidiabetic potential of Withania coagulans Dunal Flower in Streptozotacin Induced Diabetic Rats - Kitukale, M.D. (International Journal of Pharmaceutical & Biological Archive, 2017)
The present study was designed to evaluate the anti-diabetic potential of flower of Withania coagulans Dunal. The dried flowers were extracted successively by methanol and water. These extract then subjected for phytochemical screening. Animals were divided in seven groups and treated with high dose (400 mg/kg) and low dose (200 mg/kg) of methanolic and aqueous extract and compared with diabetic control group. Results of diabetic study indicates that administration of methanolic and aqueous extract of Withania coagulans Dunal daily for 28 days showed significant decrease in the blood glucose of the STZ induced diabetic rats compared to the diabetic control rats. The findings of this research suggest that the methanolic and aqueous extract of Withania coagulans Dunal flower may contains bioactive constituents with anti-diabetic potential which can be used for the treatment of diabetes mellitus.